Some sage advice: A case report of sage burning causing interstitial lung disease - Jonathan Ayling-Smith; Richard Attanoos; Nicola-Xan Hutchinson (Clinical Medicine)
Background: Cigarette smoking remains the commonest cause of chronic obstructive pulmonary disease (COPD) and respiratory bronchiolitis-associated interstitial lung disease (RB-ILD). Biomass combustion remains a high risk for causing respiratory disease. Method: We present a case of a 41-year-old woman and never-smoker with worsening breathlessness. It was identified that she made fire pits burning sage and oils for spiritual work, but beyond this had no respiratory risk factors. Results: Radiological evidence of RB-ILD was identified and a bronchoscopic lavage demonstrated the presence of striking green pigmented macrophages, presumed to be chlorophyll uptake. Conclusions: Cessation of burning sage exposure has resulted in a positive outcome. This case highlights the need for an extensive occupational or exposure history in respiratory medicine and describes histological features of interstitial lung disease not previously identified.